Experimental study on the static and dynamic performances of gas foil bearings for the centrifugal air compressor used in fuel cell vehicles. (8th November 2021) - Shi, Ting; Huang, Haiyang; Peng, Xueyuan; Feng, Jianmei; Guo, Yi
Summary: The gas foil bearings (GFBs) are one of the vital components of the air compressor applied in fuel cell vehicles. The design and operating parameters have an impact on the static and dynamic performances of GFBs, the properties of which need to be tailored to match the specific application demands. The influence of excitation frequency, nominal clearance, loading direction, and elastic structure on the performances is experimentally studied in this article. The results show that the displacement increased while the stiffness decreased with the increase in the nominal clearance. The recommended loading position is provided based on the analysis. The largest stiffness is obtained in the GFBs with the radial trisection foil. Considering the high stiffness and low damping, the best GFB aimed at anti‐vibration is obtained. The results can be used as guidelines for component matching in the design and operation of the polymer electrolyte membrane fuel cell system.